MANAGING DIVERSITY OF HUMAN RESOURCES AS AN EFFORT TO IMPROVE EMPLOYEE PERFORMANCE (CASE STUDY AT PT. LONTAR PAPYRUS PULP & PAPER INDUSTRY) - Almaududi, Said (Dinasti Publisher, 2020)
This study aims to analyze the effect of managing the diversity of human resources on the performance of employees of PT. Lontar Papyrus Pulp & Paper Industry. The study population was all employees of PT. Lontar papyrus pulp & paper industry, West Tanjung Jabung Regency, totaling 3,023 people. the size or number of samples in this study is determined based on the theory developed by Slovin with a value of e = 10%, so that a sample of 97 people is obtained. The approach in this study uses a quantitative approach to the survey method and uses Partial Least Square (PLS) data analysis. But before the analysis, the outer model test is first performed through the validity and reliability test. Furthermore, the Inner Model test is carried out through the R-Square (Coefficient of determination) and F-Square (f2 effect size) tests. The results showed that the management of diversity in human resources affected the performance of the employees of PT. Lontar Papyrus Pulp & Paper Industry. management of diversity in human resources affected the performance of the employees of PT. Lontar Papyrus Pulp & Paper Industry.